Diversité et importance des chenilles dans l'alimentation des populations du Zaïre - Malaisse, F. (Tropicultura, 1995)
Diversity and Importance of Caterpillars in the Diet of the Populations of Zaire. Eight papers dealing with edible caterpillars of Zaire are listed ; the oldiest one being dated 1945. Edible caterpillars are relevant to a tent of families. Their importance varies according to regions ; those dominated by woodlands corresponding to the largest consumption.